This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: MATH 138 Physicsbased Section 007 Assignment 5 Solutions Winter 2010 Note: A firstorder linear differential equation (D.E.) is of the form dy dx + P ( x ) y = Q ( x ) (1) and the integrating factor for such a D.E. is I ( x ) = e R P ( x ) dx . 1 . ( a ) The D.E. dy dx + y = cos ( e x ) (2) is of the form (1) with P ( x ) = 1. Since Z P ( x ) dx = Z 1 dx = x + k we can choose the integrating factor I ( x ) = e x . Multilply the D.E. (2) by I ( x ) = e x to obtain e x dy dx + e x y = e x cos ( e x ) or d dx ( e x y ) = e x cos ( e x ) . Integrate both sides with respect to x to obtain Z d dx ( e x y ) dx = Z e x cos ( e x ) dx or e x y = sin ( e x ) + C, C ∈ < since d dx sin ( e x ) = e x cos ( e x ) by the Chain Rule. Therefore the general solution of the D.E. (2) is y = e x sin ( e x ) + Ce x , C ∈ < . 1 1 . ( b ) By writing the D.E. dy dx = x y x , x 6 = 0 as dy dx + 1 x y = x (3) we see the D.E. is of the form (1) with P ( x ) = 1 x . Since Z P ( x ) dx = Z 1 x dx = ln  x  + k we can choose the integrating factor I ( x ) = e ln x = x. (Note: I ( x ) = x also works.) Multilply the D.E. (3) by I ( x ) = x to obtain x dy dx + xy = x 2 or d dx ( xy ) = x 2 . Integrate both sides with respect to x to obtain Z d dx ( xy ) dx = Z x 2 dx or xy = 1 3 x 3 + C, C ∈ < . Therefore the general solutions of the D.E. (3) is y = 1 3 x 2 + C x , C ∈ < , x 6 = 0 . 2 2 . ( a ) By writing the D.E. cos x dy dx + y sin x = 1 as dy dx + sin x cos x · y = 1 cos x or dy dx + tan x · y = sec x (4) we see the D.E. is of the form (1) with P ( x ) = tan x . Since Z P ( x ) dx = Z tan xdx = ln  sec x  + k we can choose the integrating factor I ( x ) = e ln(sec x ) = sec x. (Note: I ( x ) = sec x also works.) Multilply the D.E. (4) by I ( x ) = sec x to obtain sec x dy dx + sec x tan x · y = sec 2 x or d dx (sec x · y ) = sec 2 x. Integrate both sides with respect to x to obtain Z d dx (sec x · y ) dx = Z sec 2 xdx or sec x · y = tan x + C, C ∈ < . Therefore the general solution of the D.E. (4) is y = cos x tan x + C cos x, C ∈ < = sin x + C cos x, C ∈ < Apply the initial condition y ( π/ 4) = √ 2 to get √ 2 = sin π 4 + C cos π 4 √ 2 = 1 √ 2 + C 1 √ 2 2 = 1 + C and therefore C = 1 ....
View
Full
Document
This note was uploaded on 01/06/2011 for the course MATH 138 taught by Professor Anoymous during the Winter '07 term at Waterloo.
 Winter '07
 Anoymous
 Math

Click to edit the document details